Relationship between anthropometric indicators of cardiometabolic risk and socioeconomic profile of women practicing physical activity (Research, Society and Development, 2021)
The study evaluated the anthropometric indicators of cardiometabolic risk and their relationship with the socioeconomic profile of women practicing physical activity. Cross-sectional study with 55 adult women in the Northeast region of Brazil. Cardiometabolic risk was determined by waist circumference, conicity index and body mass index. In addition, the Food Frequency Questionnaire (QFA) was applied with quantitative analysis by the Dietsys software version 4.01. The research participants were divided according to the economic class established by the Brazilian Association of Research Companies (ABEP) and the data were analyzed using the Graphpad prism 5.0® software, with a significance level of p